2004
DOI: 10.1021/pr034039p
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Proteins Preseparated by Electrophoresis or Chromatography Followed by Tandem Mass Spectrometry

Abstract: Electrophoretic and chromatographic sample preparations were compared and together detected the presence of some 600 types of protein products in human serum. Proteins from crude serum preseparated by ionic electrophoresis, chromatography, or a combination of both were analyzed. Proteins were digested with trypsin or chymotrypsin. Naturally occurring peptides were also collected by reversed-phase chromatography. The resulting peptides were identified by tandem mass spectrometry. The peptides were either desorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(168 citation statements)
references
References 67 publications
4
164
0
Order By: Relevance
“…Significantly, AAT is a wellestablished abundant serum protein; 29 in addition, other independent, large-scale studies on serum have reported the presence of many of the proteins listed in Table 1. 21,[30][31][32][33][34] Other identified proteins of note are also listed in Table 1. Details of peptides identified are given in Supplementary Table 5s in Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, AAT is a wellestablished abundant serum protein; 29 in addition, other independent, large-scale studies on serum have reported the presence of many of the proteins listed in Table 1. 21,[30][31][32][33][34] Other identified proteins of note are also listed in Table 1. Details of peptides identified are given in Supplementary Table 5s in Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Like Aebersold and Mann [2], they conclude that no single analytical approach will identify all the major proteins in any proteome. Others have recently used similar 2-D separation of peptides offline, intact protein fractionation prior to MS, or sensitive ESI-MS/MS analysis of fractionated peptides [36][37][38][39]. As far as cost-effectiveness, the 2-D HPLC approach required much more time and labor and was much less suited to automation than the other strategies; it has the advantage of being able to process large volumes of sample, when that is available and desired.…”
Section: Comparing Technology Platformsmentioning
confidence: 99%
“…To test the feasibility of this approach, we searched all ORFs using peak list data from six PPP laboratories (17,30,37,41,52,55). NCBI human genome sequence build 33 was translated in all three reading frames and both strands; all non-redundant ORFs were assembled into chromosome specific sequence collections.…”
Section: Identification Of Novel Peptides Using Whole Genome Orf Searchmentioning
confidence: 99%
“…One school of thought has been that nearly all peptides result from highly specific digestion by the exogenous protease, typically trypsin, and thus all confident peptide identifications should conform to fully tryptic digestion patterns (e.g., [10,48]). Alternatively, complex protein mixtures processed by endogenous proteases may contain unexpected amino-and carboxy-termini, resulting in non-tryptic cleavage states (e.g., [15,18,27]).…”
Section: Confidence In Any Ms-based Proteomic Approachmentioning
confidence: 99%
“…The Plasma Proteomics Initiative is timely, as blood plasma and serum are widely recognized as body fluids of great promise for human health for diagnostics, e.g., disease prognostics and clinical monitoring [2,4,[6][7][8][9][10][11][12][13][14][15][16][17][18]. Two of the most compelling reasons for studying human plasma are 1) the universal availability of sufficient blood plasma and serum for method development and validation and 2) the long-standing use of plasma and serum as a source of clinically relevant information [6,19].…”
Section: Introductionmentioning
confidence: 99%